Cationic micelle: A promising nanocarrier for gene delivery with high transfection efficiency. (9th July 2019) - Wang, Haili; Ding, Shenggang; Zhang, Ze; Wang, Longhai; You, Yezi
Abstract: Micelles have demonstrated an excellent ability to deliver several different types of therapeutic agents, including chemotherapy drugs, proteins, small‐interfering RNA and DNA, into tumor cells. Cationic micelles, comprising self‐assemblies of amphiphilic cationic polymers, have exhibited tremendous promise with respect to the delivery of therapy genes and gene transfection. To date, research in the field has focused on achieving an enhanced stability of the micellar assembly, prolonged circulation times and controlled release of the gene. This review focuses on the micelles as a nanosized carrier system for gene delivery, the system‐related modifications for cytoplasm release, stability and biocompatibility, and clinic trials. In accordance with the development of synthetic chemistry and self‐assembly technology, the structures and functionalities of micelles can be precisely controlled, and hence the synthetic micelles not only efficiently condense DNA, but also facilitate DNA endocytosis, endosomal escape, DNA uptake and nuclear transport, resulting in a comparable gene transfection of virus.